Pengaruh Pengalaman Kerja, Keterampilan Kerja, dan Sikap Kerja terhadap Kinerja Karyawan UD Rahayu Indah Kediri - Fadhila Damaratih; Heru Sutapa; Rafkhein Novia (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the influence of work experience, professional skills, and work attitudes on employee performance at UD Rahayu Indah Kediri. This study uses a quantitative approach with a population of 76 respondents, which is also used as a sample through the saturated sampling method. Data were collected using questionnaires and analyzed with the help of Statistical Package for the Social Science (SPSS) software version 25.0. The independent variables in this study include work experience, professional skills, and work attitudes, while the dependent variables are employee performance. The results of the analysis show that the three independent variables have a significant influence on employee performance. Work experience contributes to shaping work effectiveness and efficiency, professional skills play a role in improving quality and productivity, while work attitudes affect individual motivation and responsibility in carrying out tasks. These findings indicate that improving employee performance can be achieved through strengthening work experience, developing professional skills, and forming a positive work attitude. This research provides practical implications for company management to design human resource development strategies that focus on improving competencies and work behaviors. Thus, companies can create a productive and highly competitive work environment.